2017
DOI: 10.1016/j.foodchem.2016.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Quality classification of Spanish olive oils by untargeted gas chromatography coupled to hybrid quadrupole-time of flight mass spectrometry with atmospheric pressure chemical ionization and metabolomics-based statistical approach

Abstract: The novel atmospheric pressure chemical ionization (APCI) source has been used in combination with gas chromatography (GC) coupled to hybrid quadrupole time-of-flight (QTOF) mass spectrometry (MS) for determination of volatile components of olive oil, enhancing its potential for classification of olive oil samples according to their quality using a metabolomics-based approach. The full-spectrum acquisition has allowed the detection of volatile organic compounds (VOCs) in olive oil samples, including Extra Virg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 30 publications
2
61
0
1
Order By: Relevance
“…26,27 The replicates of S. aureus are clustered at the largest distance from the rest of the bacterial strains; S. haemolyticus are distant from S. aureus with highest distinction; S. hominis and S. epidermidis are close to each other but the boundaries are clear (detailed in Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…26,27 The replicates of S. aureus are clustered at the largest distance from the rest of the bacterial strains; S. haemolyticus are distant from S. aureus with highest distinction; S. hominis and S. epidermidis are close to each other but the boundaries are clear (detailed in Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…A recent review that focused on the use of GC/MS with TOF mass analyzers describes their use for the analysis of a large number of organic contaminants and residues present at trace levels for environmental, food safety and biological applications . A recent example of the use of FS/HR GC/MS in the food analysis field combined atmospheric pressure chemical ionization (APCI) with the use of a Q‐TOF mass analyzer for the analysis of the volatile components of olive oil …”
Section: Introductionmentioning
confidence: 99%
“…Few studies (Borràs et al, 2015;Borràs et al, 2016;Garrido-Delgado et al, 2015;Sales et al, 2017;Contreras et al, 2019b) can be found to demonstrate the potential of analytical instruments in order to complement the sensorial analysis to classify olive oil samples as EVOO, VOO, and LOO. To demonstrate the usefulness of these methods, the amount of analyzed samples of different harvests should be high in order to obtain representative conclusions.…”
Section: Introductionmentioning
confidence: 99%